Improving Teachers' Ability to Design Physical Education Learning Scenarios - Syaranamual, Jusak; Syaranamual, Mariana Ditboya (KnE Social Sciences, 2024)
This study aimed to: 1) Produce a draft lesson plan (RPP) in accordance with physical education learning. 2) Produce the design of physical education learning scenarios. The population in this study was elementary school Physical Education teachers in Ambon City, Central Maluku, and Tual City. The sample was determined by 1 Physical Education teacher from each district so that there were 4 teachers; 1 teacher from SD Negeri 65 Ambon, 1 teacher from SD Negeri 7 Masohi, 1 teacher from SD Negeri Sohoku, and 1 teacher from SD N Kolser Tual City. The area sampling technique was chosen based on the best representatives from each region. Data were collected using observation and documentation techniques. The assessment instrument for the preparation of Physical Education learning scenarios used the teacher professional education (PPG) assessment rubric. Data analysis used descriptive qualitative data analysis techniques. The results of preliminary data analysis show that the first, second, third, and fourth respondents all have very poor abilities. This can be seen from the results of the assessment score obtained amounting to 125 out of a total score of 280, or it can be said that the ability was 45%. Meanwhile, the fourth respondent hads an ability of 40%. Thus, based on the assessment scores of the elements of the learning model indicator, it was known that there is no teacher's ability to plan a learning model that can be used to teach the subject matter based on the demands of the 2013 curriculum. This can be seen from the acquisition of the average assessment score at the achievement of number 1. This is because the scenario does not include what learning model is suitable for teaching the selected subject matter. Keywords: teacher ability, scenario design, physical education learning